2022
DOI: 10.1002/aenm.202103979
|View full text |Cite
|
Sign up to set email alerts
|

Charge‐Enriched Strategy Based on MXene‐Based Polypyrrole Layers Toward Dendrite‐Free Zinc Metal Anodes

Abstract: the formation of Zn dendrites, but also suppress the side reactions by shielding the Zn anode from contact with the electrolyte. In this regard, various functional materials have been reported as artificial interfaces on Zn anodes and efficiently improve the cycle performances. [24][25][26] For example, the introduction of highly latticematched materials on Zn anode enables to reduce the energy barrier of zinc crystal growing in (002) direction and induce horizontal growth of Zn. [27][28][29] By designing ion-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
103
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(104 citation statements)
references
References 37 publications
1
103
0
Order By: Relevance
“…[40,41] From scanning electron microscopy (SEM) images of CuHCF nanoparti-cles, it can be found that the CuHCF particle size is uniform, and the nanospheres do not exceed 100 nm (Figure S2, Supporting Information). In addition, the specific surface area of 743.4 m 2 g -1 and the existence of mesopore pore size of CuHCF particles are confirmed by N 2 adsorption-desorption isotherms, which are beneficial to provide more zinc adsorption sites and form zinc ion transport channels to uniform zinc ion flux [34,42,43] The surface SEM images of bare Zn and Zn@CuHCF anode before cycling are exhibited in Figure S4 (Supporting Information), it can be found that the surface of bare Zn anode is not completely smooth and flat before cycling, and the coating layer surface is compact and dense. The water contact angle (WCA) test of the Zn@CuHCF and bare Zn electrode is compared under the same condition (Figure S5, Supporting Information), the WCA of the bare Zn surface is 75.0°, which is much higher than the 23.9° of Zn@CuHCF.…”
Section: Resultsmentioning
confidence: 91%
“…[40,41] From scanning electron microscopy (SEM) images of CuHCF nanoparti-cles, it can be found that the CuHCF particle size is uniform, and the nanospheres do not exceed 100 nm (Figure S2, Supporting Information). In addition, the specific surface area of 743.4 m 2 g -1 and the existence of mesopore pore size of CuHCF particles are confirmed by N 2 adsorption-desorption isotherms, which are beneficial to provide more zinc adsorption sites and form zinc ion transport channels to uniform zinc ion flux [34,42,43] The surface SEM images of bare Zn and Zn@CuHCF anode before cycling are exhibited in Figure S4 (Supporting Information), it can be found that the surface of bare Zn anode is not completely smooth and flat before cycling, and the coating layer surface is compact and dense. The water contact angle (WCA) test of the Zn@CuHCF and bare Zn electrode is compared under the same condition (Figure S5, Supporting Information), the WCA of the bare Zn surface is 75.0°, which is much higher than the 23.9° of Zn@CuHCF.…”
Section: Resultsmentioning
confidence: 91%
“…Improved Zn plating/stripping reversibility is ascribed to the fact that the MXene@NiO modified separator can regulate Zn deposition and inhibit side reaction (Figure S16). 23,37,63 EIS characterizations for pristine and modified separators after cycles are conducted (Figure S17). The pristine separator shows a higher resistance than the modified separator, which is attributed to the Zn dendrite formation and the electrolyte consumption, consequently leading to the cell failure.…”
Section: Resultsmentioning
confidence: 99%
“…Improved Zn plating/stripping reversibility is ascribed to the fact that the MXene@NiO modified separator can regulate Zn deposition and inhibit side reaction (Figure S16). ,, EIS characterizations for pristine and modified separators after cycles are conducted (Figure S17). The pristine separator shows a higher resistance than the modified separator, which is attributed to the Zn dendrite formation and the electrolyte consumption, consequently leading to the cell failure. ,, Furthermore, as exhibited in Figure S18, Zn||Cu cells with modified separator also deliver stable and high Coulombic efficiencies of 99.71% and 99.82% at high rates and deposition capacities (5 mA cm –2 to 5 mAh cm –2 , 10 mA cm –2 to 5 mAh cm –2 ) after 500 and 1000 cycles, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…dendrite, corrosion, and low efficiency, [8][9][10][11] which challenges the cycling stability of aqueous Zn metal batteries. To stabilize Zn anode, various strategies have been developed, [12] such as designing Zn host architectures and alloys, [13][14][15][16] modifying the surface of Zn, [17][18][19][20] searching for new electrolytes or additives, [21][22][23][24][25][26][27][28][29][30][31] tailoring the Zn deposition orientation, [32][33][34][35][36] and using pulsed charging protocols. [37] These strategies can inhibit dendritic Zn formation and improve the cyclability of batteries when Zn is cycled at a shallow discharge depth, but total energy densities of batteries are sacrificed due to the low utilization of Zn.…”
mentioning
confidence: 99%